2020
DOI: 10.3390/soc10040076
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Visual Ageism in Digital Media: Designing for Dynamic Diversity to Enhance Communication Rights for Senior Citizens

Abstract: This paper advocates for the importance of visual communication rights for older people to avoid “visual ageism,” described as media practices of visually underrepresenting older people or misrepresenting them in a prejudiced way. It aims to present a set of policy recommendations using “designing for dynamic diversity” as the leading principle. By discussing studies about the ways older people are visual represented in digital media content, the paper shows how visual communication rights for older people cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
11
0
2
Order By: Relevance
“…Older women and minority older adults experience a double marginalization by being even less represented in the media and are often portrayed as frail, unattractive, and invisible compared to older white men who are more often described as experienced and powerful (7,(14)(15)(16)(17)(18)(19)(20). Social media has contributed to sharing similar types of messages and visuals, mostly reinforcing a negative discourse on aging (8,21,22). For example, at the beginning of the pandemic, an analysis of two media outlets in Spain revealed that older people were depicted negatively in the majority (71%) of cases (23).…”
Section: Introductionmentioning
confidence: 99%
“…Older women and minority older adults experience a double marginalization by being even less represented in the media and are often portrayed as frail, unattractive, and invisible compared to older white men who are more often described as experienced and powerful (7,(14)(15)(16)(17)(18)(19)(20). Social media has contributed to sharing similar types of messages and visuals, mostly reinforcing a negative discourse on aging (8,21,22). For example, at the beginning of the pandemic, an analysis of two media outlets in Spain revealed that older people were depicted negatively in the majority (71%) of cases (23).…”
Section: Introductionmentioning
confidence: 99%
“…Theories of ageism are following the digitalization of the phenomenon, that is, the presence of age biases, stereotypes, prejudice, and discrimination in their digital form. The concept of “visual ageism” for example, responds to this change and describes” the digital media practices of visually underrepresenting older people or misrepresenting them in a prejudiced way” (Ivan et al 2020 ). Yet, the existing conceptualizations are still too narrow to address the complexity of various ageism manifestations in AI systems, algorithms and automatic decision-making systems.…”
Section: Ageing Population Ageism and Technologymentioning
confidence: 99%
“…Social scientists have studied extensively the way older adults use and interact with digital technology (Katz and Marshall 2018;Loos et al 2020;Wanka and Gallistl 2018) and the way gerontechnology can assist older adults in adapting to ageing processes (Klimczuk 2012). The newly emerged theoretical framework of "Socio-gerontechnology" (Peine et al 2021) promises to provide a unique understanding of ageing and technology from a social sciences and humanities perspective and contributes to the development of new ontologies, methodologies, and theories.…”
Section: Ageing Population Ageism and Technologymentioning
confidence: 99%
“…A recent analysis of institutional ageism in global health policy by Lloyd-Sherlock et al (2016) critically evaluated one of the Sustainable Development Goals (i.e., "by 2030 reduce by one-third premature mortality from non-communicable diseases through prevention and treatment") and argued that this target probably promotes institutional ageism by "discouraging research and data collection, focusing resources on younger people, and exacerbating existing discrimination." Ivan et al (2020) defined visual ageism as a specific aspect of institutional ageism, referring to media practices of visually underrepresenting or misrepresenting older people in a prejudiced way. Based on the findings of the present research, I argue that institutional ageism may be manifest in the mediatized institutions with an established process of content production that stabilizes stereotypical representations of older people in the media.…”
Section: Social Media Logic and The Representation Of Older Peoplementioning
confidence: 99%
“…They also need to present coherent and personal life stories of older people and highlight the heterogeneity of people in terms of social background, health status, care needs and personal goals. By advocating for the visual communication rights of older people, Ivan et al (2020) argued that collaborative means can be developed for involving older people in the creation of digital visual content and enhancing older people's power to meaningfully influence their own representations. In this regard, the participation of older people has the potential to strengthen their position within the power structure of representations of older people online.…”
Section: Mitigating Ageism In Social Mediamentioning
confidence: 99%